HIMPAUDI as a Bridging Organization in Deep Learning Mentoring for PAUD Teachers: A Literature Review - Aliyah, Siti; Widari, Ida; Wardani, Elia (LP. Ma'arif Janggan Magetan, 2024)
The implementation of Deep learning in early childhood education faces significant challenges, particularly the gap between the technical complexity of Deep learning and the diverse competencies of PAUD teachers. This gap has the potential to hinder the optimal use of Deep learning as a tool for learning development and assessment. The Association of Indonesian Early Childhood Educators and Education Personnel (HIMPAUDI) as a professional organization has an extensive network and understands the local context, but its role in facilitating teacher competency in the implementation of Deep learning has not been widely explored. This literature review aims to analyze the role of HIMPAUDI in the Deep learning mentoring program for PAUD teachers, using Bridging the Gap. This is to explain how this organization can bridge the gap between the intended implementation of Deep Learning and the actual realization that occurs in the field. The literature review method with a qualitative approach was chosen in this study. Primary data sources were obtained from scientific journal articles, books, as well as relevant policy documents and official publications of HIMPAUDI. Data analysis was carried out by grouping findings into key dimensions of Bridging the Gap. The study results show that HIMPAUDI acts as a strategic bridge through four main functions: facilitator for teacher capacity development, mediator between teachers and stakeholders, platform for strengthening learning communities, and partner for advocacy and quality control. These roles enable holistic mentoring to improve the competency of early childhood education teachers in adopting a contextual and sustainable Deep Learning approach.